Tradisi Pendidikan Multikultural Pada Kampus-Pesantren STIQ An Nur Yogyakarta - Hendra Harmi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Diversity or also called multiculturalism is a sunnatullah, if diversity can be managed properly it will be a tremendous force to build a nation/state, otherwise diversity that is not managed properly will be a source of conflict that leads to the disintegration of the nation/state. This paper is to explore how an Islamic university campus-pesantren responds to and cares for diversity, so that it becomes a spirit and strength to unite differences in the midst of daily routines. The research method is grounded theory—this research as understood by Earl Babie as qualitative research that aims to build theory through inductive investigation. Based on the results of the study, it can be understood that the cultural integration between the Islamic boarding school tradition and the perspective of multiculturalism has become a good pre-condition for the growth of multicultural values in students. This process is then called